“Diseño de un sistema de riego por goteo para un cultivo de tomate de árbol (Solanum betaceum) para la finca “María Auxiliadora” del sector Troncopamba, parroquia y cantón Saraguro, provincia de Loja” - Macas Parra, Galo Michael (2024)
The province of Loja presents a marked distribution of precipitation, the Saraguro canton is no exception, manifesting periods of water deficit, evidencing a decrease in productivity, giving way to the use of small flows, which is why the present study, determined the irrigation requirements for growing tree tomatoes, which will be used to design drip irrigation. The description of the soil profile and its analysis was carried out in the laboratory, presenting a sandy loam texture; Its hydrophysical properties were: CC=38.87%; PMP =20.17%; Da = 1.15 g/cm3; AA = 19.54%; VPI = 53.57. The maximum water requirement for growing tree tomato is 3.03 mm/day, in the month of August. The agronomic design established the total unit needs per plant of 10.33 l/tree, using a flow rate of 0.68 l/s, with a daily irrigation frequency and an irrigation duration of 38 minutes. The hydraulic design determined a secondary polyethylene pipe of 1 MPa, nominal diameter of 25 mm, 28.30 m in length, and a flow velocity of 1.96 m/s; The irrigation laterals are made of polyethylene, 23.00 m long, commercial diameter of 12 mm, and self-compensated drippers of 4.00 l/h; The main pipe is 40 mm in diameter and 240 m in length. Finally, a pumping system will be installed, so a single-phase pump model AL-REDm 600- 4 with a power of 0.50 HP has been selected, which will compensate for the missing energy. Keywords: Drip irrigation, Agronomic design, Hydraulic design, Irrigation laterals, Drippers.